The bronze bow - Speare, Elizabeth George (Boston : Houghton Mifflin, 1989)
After witnessing his father's crucifixion by Roman soldiers, Daniel bar Jamin is fired by a single passion: to avenge his father's death by driving the Roman legions from the land of Israel. Time and again Daniel is drawn to the teachings of Jesus of Nazareth, only to turn away, disappointed and confused by Jesus's lack of action in opposing the Romans. This is a novel about Daniel's tormented journey from a blind, confining hatred to his acceptance and understanding of love.
Keywords: Jesus Christ -- Juvenile fiction; Revenge -- Juvenile fiction; Newbery Medal; Palestine -- Juvenile fiction; Christian fiction -- Juvenile fiction; Historical fiction -- Juvenile fiction